An Observational Study of Charakokta Angula Pramana for Standardization of Shirogreevagata Pratyanga (AYUSHDHARA, 2023)
Ayurveda is a science of life that deals with prevention and cure of diseases. To unscrew the pathology of various diseases, a thorough understanding the structural and functional built of the human physique is inevitable. To achieve such goals there should be knowledge of body (Sharir), body parts (Anga and Pratyanga) and their Pramana (anthropometry). Angula Pramana is determined by measuring the height (Utsedha), length (Ayam), breadth (Vistar) and circumference (Parinah) of Pratyangas. Here finger breadth of the individual (i.e. Swa-Angula) is used as the reference unit of measurement. Anthropometry measurement of the human body means measurement of height and weight where Acharya Charaka, Sushruta, and Vagbhatt have given different values of human height which is 84 Angula, 120 Angula, 31/2 Hasta respectively. The study was conducted on 200 healthy volunteers in age group of 18-50years. One Angula as a unit of Angula Pramana was obtained by measuring the width of Madhyamparva of middle finger of working hand. The measurements were taken in centimetres for standardization as per metric system. This article summarizes the facts related to Anguli Pramana from classical, Ayurvedic and modern literature along with result of our research work to identify the anatomical landmark of Sheerogreevagata Pratyanga measured through Anguli Pramana and its applied aspect. At present, there are many physical anomalies i.e., genetic, endocrine, congenital, developmental disorders and traumatic injury which results as anatomical disfiguration of Shira and Greeva that can distinguish from their Anguli pramana or anthropometry.